Geography and Religion in Hausa and Tangale Belief Systems: An Emic Perspective - Ibrahim, Usman (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Migration process has resulted in the development of numerous belief systems in most societies of the world. Belief system is one of the cultural resources that creates vitality to culture and gives cultural confidence to the adherents of a particular culture. In addition, belief is the complete picture of the system of the adherents’ conviction either directly or indirectly. This paper concentrates on the history of migration of Hausa groups to the following locations: Kaltungo, Shangom and Billiri all in Gombe State. The focus is the link between geography, religion and belief system in relations to the dual community. Also, similarities and differences between Hausa and Tangale belief system have been identified. The paper chooses emic perspective to explore the reasons why Hausa and Tangale which share many similarities in their belief systems to reveal the influence of geography and religion in such relations. The paper submitted that belief system is conventional and not scientific as it cannot be overcome by logic as scientific ideas and revealed that religion has helped to break through.